Reação de genótipos de arroz de terras altas a Meloidogyne incógnita - Souza, Daiane Cristina Terras (2014)
The productivity of upland rice can be compromised due to the attack of nematode root galls of the genus Meloidogyne spp .. One method of controlling nematodes is the use of resistant cultivars, but is difficult to use these cultivars due to lack of information on sources of resistance and productivity of these sources. This study aimed to identify strains of upland rice with desirable resistant nematodes causing root galls agronomic characteristics (Meloidogyne incognita) in order to provide support to the improvement of upland rice program in the region. The experiment was conducted in a greenhouse at the Federal University of Mato Grosso, Sinop campus. 36 rice genotypes originating from the highlands of Embrapa Rice and Beans were evaluated, adopting a completely randomized design (CRD) with 4 replications. After 30 days from planting was performed the inoculation of approximately 1000 eggs and second-stage juveniles (J2) of Meloidogyne incognita per plant. After a period of 55 days after inoculation, were obtained fresh weights of roots and shoots of plants, estimated egg mass index (IMO) and reproduction factor (RF), where plants with RF <1, were considered resistant and RF ≥ 1 susceptible. Analyses of variance were performed using the program SISVAR with transformation of data in the square root of x + 1 for RF and IMO. Means were compared by the Scott-Knott test at 5% probability. Not significant for the index of egg mass in different rice genotypes evaluated differences were observed, showing that this tool should not be used as the sole method for the selection of strains for resistance to root-knot nematode (Meloidogyne incognita). Estimates of RF varying from 0.03 to 2.61. In this study it was found that 83% of tested strains behaved as resistant, with a reduction in the initial nematode populations, with RF <1. Keywords: Factor